Sistem Informasi Penerimaan Barang Masuk di Dinas Perindustrian dan Perdagangan Kabupaten Labuhanbatu - Gardana, Eldi; Dar, Muhammad Halmi; Masrizal, Masrizal (Politeknik Ganesha Medan, 2022)
In a company or organization, data and information is an important thing to run business processes. Valid data is a capital for the creation of information that is very useful for the continuity of the company's performance. The value of data in a company or organization can be expensive when the data is needed. As in the case of calculating the number of incoming goods at the Department of Industry and Trade of Labuhanbatu Regency, it is still done manually, such as using transfer receipts and this requires a long process in presenting reports and even errors in writing the name of the goods on the invoice. The reality is that its implementation in the field faces major obstacles when it comes to the goods in and out system in the warehouse. For the processing system of incoming goods is not directed and unorganized so that the function and purpose as well as the security of information out of goods are not organized. Inventory system in goods is an activity that consists of data on receipt of goods, data on sales of goods, returns data, and data on stock of goods that report all activities out of goods. The purpose of making the system is to make an efficient computerized system application design and make its implementation into programming. The result of writing this information is to be able to assist and process data in and out of goods as well as supervision in and out of goods so that the delivery is more effective and effective. From the writing submitted, it can be concluded that the implementation can be used for data processing in and out of goods